2021
DOI: 10.1155/2021/5643134
|View full text |Cite
|
Sign up to set email alerts
|

Acute Respiratory Tract Infections among Hospitalized Palestinian Patients (2011–2016): A Retrospective Study

Abstract: Respiratory tract infections (RTIs) are a major public health concern. This study aims to investigate the profiles and epidemiological characteristics of acute RTIs and respiratory pathogens in Palestinian hospitalized patients. Clinical samples from hospitalized patients with symptoms of acute RTIs admitted between January 2011 and December 2016 were referred to the Palestinian Central Public Health Laboratory (PHCL) to identify the causative pathogen. Patients’ demographic information and the results of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…The highest incidence of URIs was recorded during the cold season (December to March) throughout the study years. A study that included 15,413 people in Pakistan found that the winter season (December to March) had the highest incidence of respiratory tract infections between 2011 and 2016 [ 50 ]. Obesity might be another factor that contributes to snoring in winters.…”
Section: Discussionmentioning
confidence: 99%
“…The highest incidence of URIs was recorded during the cold season (December to March) throughout the study years. A study that included 15,413 people in Pakistan found that the winter season (December to March) had the highest incidence of respiratory tract infections between 2011 and 2016 [ 50 ]. Obesity might be another factor that contributes to snoring in winters.…”
Section: Discussionmentioning
confidence: 99%